GLP-1(28-36)amide, the Glucagon-like peptide-1 metabolite: friend, foe, or pharmacological folly? - Taing MW; Rose FJ; Whitehead JP (Dove Medical Press, 2014)
Meng-Wong Taing,1,2 Felicity J Rose,1,3 Jonathan P Whitehead11Metabolic Medicine, Mater Research Institute, University of Queensland, 2School of Pharmacy, University of Queensland, Brisbane, QLD, Australia; 3University of Queensland Diamantina Institute, Translational Research Institute, Brisbane, QLD, AustraliaAbstract: The glucagon-like peptide-1 (GLP-1) axis has emerged as a major therapeutic target for the treatment of type 2 diabetes. GLP-1 mediates its key insulinotropic effects via a G-protein coupled receptor expressed on β-cells and other pancreatic cell types. The insulinotropic activity of GLP-1 is terminated via enzymatic cleavage by dipeptidyl peptidase-4. Until recently, GLP-1-derived metabolites were generally considered metabolically inactive; however, accumulating evidence indicates some have biological activity that may contribute to the pleiotropic effects of GLP-1 independent of the GLP-1 receptor. Recent reports describing the putative effects of one such metabolite, the GLP-1-derived nonapeptide GLP-1(28-36)amide, are the focus of this review. Administration of the nonapeptide elevates cyclic adenosine monophosphate (cAMP) and activates protein kinase A, β-catenin, and cAMP response-element binding protein in pancreatic β-cells and hepatocytes. In stressed cells, the nonapeptide targets the mitochondria and, via poorly defined mechanisms, helps to maintain mitochondrial membrane potential and cellular adenosine triphosphate levels and to reduce cytotoxicity and apoptosis. In mouse models of diet-induced obesity, treatment with the nonapeptide reduces weight gain and ameliorates associated pathophysiology, including hyperglycemia, hyperinsulinemia, and hepatic steatosis. Nonapeptide administration in a streptozotocin-induced model of type 1 diabetes also improves glucose disposal concomitant with elevated insulin levels and increased β-cell mass and proliferation. Collectively, these results suggest some of the beneficial effects of GLP-1 receptor analogs may be mediated by the nonapeptide. However, the concentrations required to elicit some of these effects are in the micromolar range, leading to reservations about potentially related therapeutic benefits. Moreover, although controversial, concerns have been raised about the potential for incretin-based therapies to promote pancreatitis and pancreatic and thyroid cancers. The effects ascribed to the nonapeptide make it a potential contributor to such outcomes, raising additional questions about its therapeutic suitability. Notwithstanding, the nonapeptide, like other GLP-1 metabolites, appears to be biologically active. Increasing understanding of such noncanonical GLP-1 activities should help to improve future incretin-based therapeutics.Keywords: diabetes, incretins, metabolites, insulinotropism